Effect of Process Variables on the Crevice Corrosion in Type-304 Stainless Steels - Adeniyi, Adewale G.; Ighalo, Joshua O. (Recent Innovations in Chemical Engineering, 2020)
Background: Corrosion is a major problem in most industries making use of metals across the world. The protection of metals and pipelines in the petroleum industry against different forms of corrosion has been of interest to stakeholders for many years. Objective: In this study, the effects of NaCl concentration, crevice scaling factor and immersion time on the percentage area attacked and the maximum depth of crevice attack in type- 304 stainless steels were investigated. Methods: The assembly and experimentation of crevice attack in type-304 stainless steels were according to ASTM G-78. Furthermore, the open circuit potential of the system was determined and numerical optimisation of the process factors was conducted. Results: The open-circuit potential for creviced SS-304 revealed a greater susceptibility to crevice corrosion at higher NaCl concentrations. It was observed that the percentage area attacked and the maximum depth of attack increased with increasing NaCl concentration and time. However, the higher scaling factors led to a lesser area and depth of attack. Numerical optimisation revealed that the optimum value (minimum) of % area attacked and the maximum depth of attack were 0.00005847% and 0.00984 mm at 2.43 wt% NaCl, 19.3 crevices scaling factor and 15 days, respectively. Conclusion: It can be concluded that by taking appropriate measures of maintenance and avoidance of moist environment (supplying O and H2O), the crevice corrosion of SS-304 can be mitigated.
Keywords: process systems